The Impact of Sports Massage on Physiological Recovery Parameters among Undergraduate Students: A Systematic Literature Review - Esa Aliza; Najwa Amalia Lubis (IGI in Education Insight, 2026)
Purpose of the study: This systematic literature review aims to evaluate the effectiveness of sports massage interventions on physiological recovery parameters among undergraduate students engaged in physical activities and sports training. Materials and methods: A systematic search was conducted across four electronic databases (PubMed, Scopus, Web of Science, and Google Scholar) from January 2015 to December 2024. Studies examining sports massage effects on physiological recovery markers in undergraduate students were included. The PRISMA guidelines were followed for study selection and data extraction. Quality assessment was performed using the PEDro scale for randomized controlled trials and the Newcastle-Ottawa Scale for observational studies. Results: Fifteen studies met the inclusion criteria, encompassing 847 undergraduate student participants (mean age: 20.8 ± 2.3 years). Sports massage interventions demonstrated significant improvements in multiple physiological parameters: reduced muscle soreness (standardized mean difference [SMD] = -1.24; 95% CI: -1.67 to -0.81), decreased blood lactate concentration (SMD = -0.89; 95% CI: -1.23 to -0.55), improved heart rate recovery (SMD = 0.76; 95% CI: 0.43 to 1.09), enhanced range of motion (SMD = 1.12; 95% CI: 0.78 to 1.46), and accelerated muscle strength recovery (SMD = 0.68; 95% CI: 0.34 to 1.02). Massage duration of 15-30 minutes showed optimal effects, with Swedish and sports-specific massage techniques demonstrating superior outcomes. Conclusions: Sports massage represents an effective non-pharmacological intervention for enhancing physiological recovery in undergraduate student athletes. The evidence supports its integration into training and competition protocols to optimize performance and reduce injury risk. Future research should investigate long-term effects and comparative effectiveness of different massage modalities.